The Meiji Restoration - Causes, Nature and Significance - Kumar, Parveen (Innovative Research Thoughts, 2018)
Since 1603 to 1868 Japan was a feudal society with a hierarchy of lords, samurai, and peasants. A military dictator, or shogun, ruled over everyone. The shogun was a member of the Tokugawa clan, so this time was known as the Tokugawa shogunate. Although Japan also had an emperor hanging around, the emperor had little to no power. The nation was closed off to foreigners. But in 1867, the 15th Tokugawa shogun resigned, and by 1868, the Meiji Restoration had begun. It was led by young samurai who saw the need for change. The emperor was reinstated as sovereign, and he took the name Meiji. 'Restoration' sounds like you're going back, making things look how they used to look. You know, like old cars polished and souped-up to look like new again. However, the Meiji Restoration was a total reinvention of Japan.